Nahum Stutchkoff's Yiddish Play and Radio Scripts in the Dorot Jewish Division, New York Public Library - Seigel, Amanda (Miryem-Khaye) (Judaica Librarianship, 2011)
The Nahum Stutchkoff collection in the Dorot Jewish Division of The New York Public Library contains Yiddish translations, plays, song lyrics, and radio programs created by Yiddish linguist and playwright Nahum Stutchkoff (1893–1965). This article describes the collection in the context of the Jewish Division’s holdings, using bibliographic details about his known works to trace Stutchkoff’s career as a Yiddish actor, translator, director, playwright, and linguist. Stutchkoff’s radio scripts in particular provide rare documentation of the golden era of Yiddish radio explored by Henry Sapoznik and Ari Y. Kelman. A detailed bibliography of Stutchkoff’s published and unpublished works is included.